(untitled) (Sociologisk Forskning, 2019)
The aim of this study is to reach a deeper understanding of the ambition of early return-to-work, defined in the rehabilitation process, and what it means for some of those affected, women on sick-leave. Based on a governmental inquiry and responses to an open question from a survey, a discourse analyze is made with focus on how power and resistance appear in the material. The analysis show that the governmental inquiry can be understood as shaping discursive practices where early return-to-work is central. From that, the individual is positioned as a ”passive” re- ceiver of rehabilitation, and/or as ”slow” in regard to norms created in the rehabilitation process. In relation to this, the women on sick-leave show resistance. That is, they oppose the normative speed of rehabilitation. From this, we mean that there is a need for variation when it comes to time in the process of return to work.